Application Value of Information-Based Health Education and Continuity of Care in Patients With Peptic Ulcer - Liu, Aihong; Kuang, Yuhua; Huang, Ruiping; Ge, Qunying (Frontiers in Public Health, 2021)
Objective: This study is to assess the application value of information-based health education and continuity of care in patients with PU (peptic ulcer). Methods: Patients (116) with PU who have been treated in the hospital between January 2019 and October 2020 were taken as research objects and equally assigned to a control group and an observation group in a random manner. In contrast to the routine care applied to the control group, the observation group received information-based health education and continuity of care intervention. The clinical efficacy, the mastery of health knowledge, self-care ability, medication compliance, quality of life, mental state, and nursing satisfaction of the two groups were compared. Results: After the intervention, the total effective rate, health knowledge adequate rate, Exercise of Self-Care Agency (ESCA) scores of all dimensions, the MOS 36-item short-form health survey (SF-36) scores of all dimensions, medication compliance rate, and total nursing satisfaction of the observation group all notably exceeded those of the control group, with a p < 0.05. Patients of the group with continuity of care intervention showed lower Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) scores, as compared to the group with conventional care (p < 0.05). Conclusion: Information-based health education and continuity of care elevates the medication adherence and nursing satisfaction of patients with PU, enhances disease-related knowledge of patients and their self-care ability, and eventually ameliorates the quality of life and psychological state. It is worthy of clinical application.